Hidradenitis suppurativa and Down syndrome: A systematic review and meta‐analysis. Issue 6 (6th September 2020) - Lam, Megan; Lai, Charis; Almuhanna, Nouf; Alhusayen, Raed
Abstract: Background: Hidradenitis suppurativa (HS), characterized by inflammatory nodules, sinus tracts, and abscesses, has been linked to several factors, including immune dysfunction and obesity, which are thought to contribute to its development. Several follicular disorders have also been associated with Down syndrome (DS), a common chromosomal disorder, including HS, although studies on this topic are limited. Objectives: To characterize HS in Down syndrome patients and to further examine the association between HS and DS compared to HS patients without DS. Methods: We systematically searched MEDLINE, Embase, Web of Science, and CENTRAL electronic databases from their dates of conception to February 2020. Random‐effects meta‐analyses were performed analyzing (a) HS characteristics between DS and non‐DS participants, and (b) prevalence or association between HS and DS compared to non‐DS individuals. Results: Twelve studies were included in this systematic review, with a total of 358 participants presenting with both HS and DS. Pooled analysis of mean differences between DS and non‐DS participants presenting with HS found a significantly younger age of HS symptom onset for DS patients (−6.24; 95% CI, −10.01‐−2.24). A meta‐analysis examining the association between HS and DS found a significantly increased likelihood of HS in DS patients (OR 9.61; 95% CI, 5.70‐16.20). Conclusions: Our findings suggest an association between HS and DS, with DS patients suffering from an earlier onset of HS symptoms compared to non‐DS patients.